2011
DOI: 10.2337/db11-0378
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Antioxidant Properties of HDLs Are Impaired in Type 2 Diabetes

Abstract: OBJECTIVEIn mice, 4F, an apolipoprotein A-I mimetic peptide that restores HDL function, prevents diabetes-induced atherosclerosis. We sought to determine whether HDL function is impaired in type 2 diabetic (T2D) patients and whether 4F treatment improves HDL function in T2D patient plasma in vitro.RESEARCH DESIGN AND METHODSHDL anti-inflammatory function was determined in 93 T2D patients and 31 control subjects as the ability of test HDLs to inhibit LDL-induced monocyte chemotactic activity in human aortic end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 29 publications
9
139
2
3
Order By: Relevance
“…38, 43 Morgantini et al reported that the anti-inflammatory properties of HDL were impaired in patients with T2DM. 44 Consistent with these findings, the present study showed that inflammatory markers such as hsCRP and lipoprotein (a) were higher in patients than in healthy controls. Lipoprotein (a) has proatherogenic and prothrombotic effects.…”
Section: Resultssupporting
confidence: 90%
“…38, 43 Morgantini et al reported that the anti-inflammatory properties of HDL were impaired in patients with T2DM. 44 Consistent with these findings, the present study showed that inflammatory markers such as hsCRP and lipoprotein (a) were higher in patients than in healthy controls. Lipoprotein (a) has proatherogenic and prothrombotic effects.…”
Section: Resultssupporting
confidence: 90%
“…However, HDL from patients with CAD on statin therapy remained proinflammatory when compared to HDL from healthy subjects, despite a significant improvement in plasma lipid levels. Interestingly, impaired antioxidant properties and increased oxidized fatty acids content were found in HDL from patients with type 2 diabetes (Morgantini et al 2011). The authors speculated that the elevated levels of oxidized fatty acids in HDL from these patients may account for the impaired antioxidant properties of the lipoprotein (Morgantini et al 2011).…”
Section: Impairment Of the Anti-oxidative Effects Of Hdl In Patientsmentioning
confidence: 99%
“…Interestingly, impaired antioxidant properties and increased oxidized fatty acids content were found in HDL from patients with type 2 diabetes (Morgantini et al 2011). The authors speculated that the elevated levels of oxidized fatty acids in HDL from these patients may account for the impaired antioxidant properties of the lipoprotein (Morgantini et al 2011). Moreover, in a different study, the ability of HDL to prevent LDL oxidation was found to be reduced in patients with acute coronary syndrome but not in patients with stable coronary artery syndrome (Patel et al 2011).…”
Section: Impairment Of the Anti-oxidative Effects Of Hdl In Patientsmentioning
confidence: 99%
“…14, 15 Furthermore, it has been reported that the antiinflammatory and antioxidative capacities of HDL were impaired in patients with diabetes mellitus type 2. 16 It is well known that HDL may be modified and lose its atheroprotective effects under chronic inflammation (ie, it can exhibit functional or dysfunctional properties). 17-19 It has been reported that markers of functional HDL are apolipoprotein A-I (apoA-I) and paraoxonase1, and those of dysfunctional HDL are apoC-III, serum amyloid A1 and lipoprotein-associated phospholipase A2 (Lp-PLA2).…”
Section: Assessment Of Cholesterol Efflux Capacitymentioning
confidence: 99%